2013
DOI: 10.1111/1574-6968.12128
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sporulation stages ofStreptomycesdifferentiation: state-of-the-art and future perspectives

Abstract: Streptomycetes comprise very important industrial bacteria, producing two-thirds of all clinically relevant secondary metabolites. They are mycelial microorganisms with complex developmental cycles that include programmed cell death (PCD) and sporulation. Industrial fermentations are usually performed in liquid cultures (large bioreactors), conditions in which Streptomyces strains generally do not sporulate, and it was traditionally assumed that there was no differentiation. In this work, we review the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 95 publications
1
58
0
1
Order By: Relevance
“…Evidence is accumulating that, like eukaryotes, bacteria undergo a process of programmed cell death (PCD). Bacterial multicellularity implies a lifestyle involving cellular heterogeneity and the occasional sacrifice of selected cells for the benefit of survival of the colony (7072). PCD is likely a major hallmark of multicellularity (8), and has been described in the biofilm-film forming Streptococcus (14) and Bacillus (10), in Myxobacteria that form fruiting bodies (59), in the filamentous cyanobacteria (3, 40), and in the branching Streptomyces (35, 38, 61).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is accumulating that, like eukaryotes, bacteria undergo a process of programmed cell death (PCD). Bacterial multicellularity implies a lifestyle involving cellular heterogeneity and the occasional sacrifice of selected cells for the benefit of survival of the colony (7072). PCD is likely a major hallmark of multicellularity (8), and has been described in the biofilm-film forming Streptococcus (14) and Bacillus (10), in Myxobacteria that form fruiting bodies (59), in the filamentous cyanobacteria (3, 40), and in the branching Streptomyces (35, 38, 61).…”
Section: Resultsmentioning
confidence: 99%
“…Cell differentiation is triggered by nutrient depletion and other signals, and both the production of secondary metabolites and morphological differentiation are initiated. whi mutants defective in different sporulation stages are employed in genetic and biochemical analyses of these developmental stages (Yagüe, López‐Garcia, Rioseras, Sánchez, & Manteca, ). The regulation of secondary metabolism in streptomycetes is diverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…whi mutants defective in different sporulation stages are employed in genetic and biochemical analyses of these developmental stages (Yagüe, López-Garcia, Rioseras, Sánchez, & Manteca, 2013). The regulation of secondary metabolism in streptomycetes is diverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…A refined investigation showed that the development of vegetative mycelium can be further distinguished into different steps; a young, compartmentalised mycelium undergoes programmed cell death. Viable parts differentiate subsequently into multinucleated second mycelia divided by thin, infrequent and single-layer septa [158][159][160]. Some of these mycelia grow into the air to form aerial mycelia covered by a hydrophobic shell [161,162].…”
Section: Development Of Bacterial Morphologymentioning
confidence: 99%